Conditions for the Release of the Whistleblower from Criminal Liability - Gagas, Ignas (Teisė, 2025)
The application of the release from criminal liability requires the fulfilment of all four conditions set out in Article 392 (1) of the Criminal Code of the Republic of Lithuania: 1) recognition of the person as a whistleblower under the Law on the Protection of Whistleblowers of the Republic of Lithuania; 2) confession of the committed criminal act; 3) active assistance in disclosing the criminal act committed by another person; 4) the criminal act that the person helped to disclose is more dangerous by its nature than the criminal act committed by the person himself. This scientific article reveals the content and problematic aspects of the conditions for the release of the whistleblower from criminal liability. In addition, the compliance of the provisions of the Law on the Protection of Whistleblowers with the requirements set out in Directive (EU) 2019/1937 regarding the definition of the whistleblower status is assessed. The conditions are not thoroughly disclosed in Case Law, and there is limited academic research on this topic. Considering this, the content of the conditions has been analysed through the Case Law and Criminal Law doctrine regarding essentially identical conditions established in other articles of the General Part of the Criminal Code.